Interferon versus methotrexate in intermediate uveitis with macular edema: results of a randomized controlled clinical trial - Mackensen, Friederike; Jakob, Eva; Springer, Christina; Dobner, Bianca C.; Wiehler, Ute; Weimer, Petra; Rohrschneider, Klaus; Fiehn, Christoph; Max, Regina; Storch-Hagenlocher, Brigitte; Becker, Matthias D. (American journal of ophthalmology, 2013)
Purpose - To compare interferon (IFN) beta with methotrexate (MTX) in the treatment of intermediate uveitis with macular edema. - Design - Monocentric, prospective, randomized, controlled clinical trial. - Methods - setting: Specialized uveitis center at the University of Heidelberg. patient or study population: Patients with either primary intermediate uveitis or uveitis associated with multiple sclerosis. main inclusion criteria: Visual acuity of 20/30 or worse (0.2 logarithm of the minimal angle of resolution) and macular edema of more than 250 μm (central 1-mm in optical coherence tomography; Stratus). Randomization into either IFN beta 44 μg subcutaneously 3 times weekly or 20 mg MTX subcutaneously once weekly. main outcome measures: At 3 months, the primary outcome parameter of mean change in visual acuity was evaluated and efficacy was determined. Secondary parameters were macular edema by optical coherence tomography, inflammatory activity, and retinal sensitivity by microperimetry (MP-1; Nidek). In case of treatment failure, switching to the other treatment arm was possible. - Results - Nineteen patients were included. Ten were randomized to MTX, and 9 were randomized to IFN beta. At 3 months, visual acuity improved a mean 0.31 logarithm of the minimal angle of resolution (range, −0.02 to −0.96, 15.6 letters on the Early Treatment Diabetic Retinopathy Study chart) in the IFN beta group versus a mean 0.09 logarithm of the minimal angle of resolution (range, 0.12 to −0.38, 4.7 letters) in the MTX arm (P = .0435, Mann-Whitney U test). Macular thickness decreased by a mean of 206 μm (range, −41 to −416 μm) in the IFN arm, but increased by 47 μm (range, 108 to −28 μm) in the MTX group (P < .0001). - Conclusions - Although the sample size is small, results of the trial support superiority of IFN beta over MTX in the treatment of macular edema in the setting of intermediate uveitis